EFFICIENCY OR EXCLUSION?, A CRITICAL STUDY OF CORPORATE COMMUNICATION IN MASS LAYOFF DECISIONS IN THE TELEVISION INDUSTRY - Saeni, Eni; RR Roosita Cindrakasih; Marlina Rahmi; Agung Rahardjo (Akrab Juara : Jurnal Ilmu-ilmu Sosial, 2025)
This study examines corporate communication related to the decision to make mass layoffs in the television industry using a critical discourse analysis approach. The main focus of the study is to understand how the narratives of efficiency and social exclusion are framed and constructed in print and online media discourse. Data were collected from various news reports and official corporate statements during the period of mass layoffs. The results of the analysis show the dominance of the efficiency narrative used by companies to legitimize the decision to make layoffs, with an emphasis on restructuring and business optimization. However, alternative discourses emerging from the media and trade unions reveal the reality of social and economic exclusion experienced by affected workers, which is often hidden from the official corporate narrative. This study confirms that corporate communication functions as a tool for legitimization and image management, but tends to ignore the crucial social dimension of exclusion. These findings reinforce the importance of a critical approach in understanding the dynamics of power through language in the context of mass layoffs. This study also highlights the role of the media as an arena for discourse battles between corporate interests and workers’ rights.